Dane w chmurze czy dane zlinkowane? - Nahotko, Marek (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
Two phenomena related to the functioning of libraries in a wide area network were compared: cloud library and Linked Open Data. Both of these phenomena are intertwined, but they are different. They are linked by the tendency to move everincreasing amounts of data into the Web environment. A new way to include the metadata to the cloud is Linked Open Data. It is about putting all the metadata in the OPEN network: bibliographic descriptions, authority files, dictionaries of all kinds (for example subject headings vocabularies). These data, after appropriate processing (RDF syntactic), form a global metadata cloud, which greatly changes how the Internet functions as an information environment, including the role of libraries.